Risk Management Strategies for Healthcare Organizations: A Comparative Analysis of Patient Safety Measures in Kenya - Kimani, Peter (International Journal of Modern Risk Management, 2023)
Purpose: The study sought to investigate the Risk Management Strategies for Healthcare Organizations: A Comparative Analysis of Patient Safety Measures in Kenya Materials and Methods: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library Results: The results revealed that risk management strategies play a crucial role in improving patient safety within healthcare organizations. By comparing different strategies, the research may highlight which ones are particularly effective in reducing errors and enhancing overall safety. The study also concludes that leadership styles and organizational culture have a significant impact on the success of risk management strategies. Healthcare organizations with supportive leadership and a culture of safety tend to perform better in patient safety measures. Unique contribution to theory, practice and policy: The study recommends that there should be a culture of safety that encourages reporting of errors and near misses, learning from mistakes, and implementing solutions to prevent recurrence. A culture of safety can foster trust, transparency, and accountability among healthcare staff and patients. Conduct regular risk assessments to identify potential hazards, vulnerabilities, and threats to patient safety and organizational performance. Risk assessments can help prioritize areas for improvement, allocate resources, and monitor progress.